DIGITAL TRANSFORMATION IN INTERNATIONAL BUSINESS: CURRENT TRENDS AND STRATEGIC GUIDELINES - Bondar, Oleksandr (Public Management and Policy, 2026)
The current stage of global economic development is characterised by the rapid growth of digital technologies, which is leading to a profound transformation of international business models. The transition from traditional approaches to digitally oriented forms of economic activity requires companies to review their strategies, improve management mechanisms and develop new tools for competitive interaction in global markets. In the context of increasing technological dynamics, the issue of adapting business structures to digital innovations capable of ensuring not only operational efficiency but also long-term sustainability is becoming increasingly relevant. The COVID-19 pandemic was a turning point, as it accelerated the adoption of digital communication channels, process automation, cloud technologies, and data analytics. This led to new requirements for the organisation of international business processes, as only companies with a high level of digital readiness were able to adapt to the crisis conditions. At the same time, the integration of artificial intelligence, 5G technologies, the Internet of Things, hyper-automation and contactless services accelerated, which determined the further development of the global market. At the same time, the problem of uneven digitalisation is becoming more acute around the world. In high-income countries, digital innovation has become the basis for business development, while countries with low levels of digital accessibility face constraints related to inadequate infrastructure and a lack of skills. This asymmetry creates risks of further deepening global disparities and slows down the integration of individual economies into digital value chains. The need for effective regulation of digital transformations, the formation of modern institutional mechanisms, the harmonisation of technical standards and state support for innovation are becoming key conditions for the sustainable development of international business. It is emphasised that digital transformation is one of the determining factors of future economic growth, and its strategic implementation ensures the competitiveness of companies and the adaptability of the global economy as a whole.